Radiation therapy quality indicators for invasive breast cancer. Issue 2 (May 2017) - Best, Lara; de Metz, Catherine; Olivotto, Ivo A.; Roy, Isabelle; Whelan, Tim; Arsenault, Julie; Brundage, Michael
Abstract: Background and purpose: Radiation therapy (RT) for breast cancer has evolved considerably over the past two decades. A concise list of optimal care indexes is lacking. The purpose of this project was to generate a suite of quality of care indicators for breast cancer RT. Materials and methods: A modified Delphi approach was used including a comprehensive literature and guideline review (1995–2015), an initial review of potential quality indicators (QIs) by a steering committee, a survey of Canadian Radiation Oncologists, and a face-to-face consensus development meeting with breast cancer experts to develop a list of breast RT quality indicators. Results: The literature review identified 163 potential QIs, which was reduced to 73 by the steering committee. After all rounds of the Delphi process the final suite included 33 QIs. Of these, 28 (85%) received at least 80% acceptance from the Radiation Oncologists who participated in the final online survey. Conclusions: A suite of measureable RT quality indicators to be considered during management of invasive breast cancer was developed. These indicators could be used to assess the quality and consistency of breast cancer RT practices.